Influence of Fertilizer Loaded Nanoclay Superabsorbent Polymer Composite (NCPC) on Dynamics of P and N Availability and their Uptake by Pearl Millet (Pennisetum glaucum) in an Inceptisols - Sarkar, Subhas; Datta, S. C. (International Journal of Bio-resource and Stress Management, 2023)
The main aim of this research was to study the P and N releasing behaviour from fertilizer loaded nanoclay superabsorbent polymer composite (NCPC) and to test its effectiveness as a carrier of slow release fertilizer using pearl millet (Pennisetum glaucum) as test crop grown under Inceptisols. Results revealed that availability of Olsen P, 0.01M CaCl2-extractable P and mineral N in soils increased significantly due to addition of fertilizer as NCPC over conventional fertilizer (CF), at same dose of fertilizer application. Availability of P and N in soils receiving low dose of fertilizer (LDF) as NCPC (NCPC-L) was statistically at par with that of high dose of fertilizer (HDF) as CF (CF-H), particularly at critical crop growth stages. Addition of NCPC-H resulted in 18% additional biomass yield and 17% and 11% additional P and N uptake by pearl millet over CF-H, respectively. Similarly, at LDF, biomass yield, P and N uptake increased to 26, 23 and 16%, respectively, under NCPC (NCPC-L) treated soils than that in CF (CF-L) treated soil. Significant build-up in different non labile pools of inorganic P fractions (Al-P, Fe-P, occluded-P, Ca-P) was recorded on addition of CF as compared to NCPC application, irrespective of fertilizer doses.